Social-ecological factors associated with having a regular healthcare provider among lesbian, gay, bisexual and transgender persons in Jamaica. Issue 6 (3rd June 2022) - Lacombe-Duncan, Ashley; Logie, Carmen H.; Li, Jane; Mitchell, Brandon; Williams, Davina; Levermore, Kandasi
ABSTRACT: Lesbian, gay, bisexual, and transgender (LGBT) people experience a multitude of barriers to healthcare access, particularly in highly stigmatising contexts, such as Jamaica. Access to a regular healthcare source can contribute to uptake of health knowledge and services. Yet social-ecological factors associated with access to a regular healthcare provider among LGBT persons in Jamaica are underexplored. We conducted a cross-sectional survey with LGBT persons in Jamaica to examine socio-demographic and social-ecological factors associated with having a regular healthcare provider. Nearly half (43.6%) of 911 participants reported having a regular healthcare provider. In multivariate analyses, socio-demographic factors (higher age; identifying as a cisgender sexual minority man or woman compared to a transgender woman) were associated with higher odds of having a regular healthcare provider. Socio-demographic (living in Ocho Rios or Montego Bay compared to Kingston), stigma/discrimination (a bad past healthcare experience), and structural factors (insufficient money for housing; reporting medication costs as a barrier; no health insurance) were associated with decreased odds of having a regular healthcare provider. Findings support a multi-level approach to understanding and addressing barriers to having a regular healthcare provider among LGBT people in Jamaica.